Beyond Benign: A Case of Subependymal Giant Cell Astrocytomas Provoking Hydrocephalus in Tuberous Sclerosis Complex - Antonio Navarro-Ballester; Rosa Álvaro-Ballester; Miguel Ángel Lara-Martínez (Acta Medica Lituanica)
22-year-old male diagnosed with Tuberous Sclerosis Complex (TSC), a genetic disorder characterized by benign tumors in various organs, with a focus on neurological implications. Central to the study is the development of Subependymal Giant Cell Astrocytomas (SEGAs), leading to hydrocephalus in the patient. The diagnosis of TSC was made in the patient’s childhood, and he was monitored regularly. The study highlights a significant growth in a subependymal nodule, leading to monoventricular hydrocephalus. MRI scans played a crucial role in identifying the progression of SEGAs and the subsequent hydrocephalus. The treatment approach involved endoscopic surgical removal of the SEGA, with histopathology confirming the diagnosis. Post-surgical outcomes over an eight-year follow-up period showed a normalization in ventricular size and the stability of other subependymal nodules, without any complications. This case underscores the importance of regular monitoring for TSC patients, early intervention for complications like hydrocephalus, and the need for a multidisciplinary treatment approach. The case study provides valuable insights into the management of neurodevelopmental disorders and the complexities surrounding TSC and SEGAs.